’n Historiografiese verkenning van watergeskiedenis - Tempelhoff, J. W. N. (Koers, 2005)
A historiographical survey of water history In this article historiographical information is utilised to indicate the potential of water as a subject of historical research. In particular applicable practical needs in contemporary society that pose a challenge to the historian to look at the past from a different perspective, are emphasised. Attention is given to the socio-economic and political aspects of the hydrosphere and areas in which historians can render a valuable contribution. The history of water is noted for its interdisciplinary character. A variety of disciplines in the natural sciences and humanities are of value to the historian. Ultimately, when relevant questions are posed within the framework of historical water research, it is clear that the field has considerable potential to stimulate transdisciplinary scientific work.